DETERMINATION OF FITTING ISSUES FOR MALAYSIAN PLUS SIZE WOMEN - Fatin Balqis Jais; Shaliza Mohd Shariff (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Fashion communication should take into account consumers’ requirements and tastes. Unfortunately, the categorization of plus-size consumers is overflowing with issues and frustration. The aim is to discover current fitting concerns based on existing Plus Size Women (PSW) size in Malaysia. PSW is having problems identifying the appropriate size. The snowball sample approach was applied for gathering 116 adult women aged 20 to 50 in Selangor. The research results show the body weight and BMI of the PSW, which represents a significant value of data 0.00%. Data were analysed using SPSS version 20. Findings show the pear body shape is the most populated with 32.48% (n=28). The major critical part of measurements in fitting is hip with 48.72% (n=42). Findings revealed there was also PSW having issues in fitting comfort during purchase of their clothing. The study offers a useful ranking of terms that fashion companies can establish for the PSW needs. This study contributes to research on plus size consumer experiences and challenges faced by PSW consumers.